The Influence of Biomass Burning on the Organic Content of Urban Aerosols - Suzana Sopčić; Ranka Godec; Ivana Jakovljević; Ivan Bešlić (Biomass)
This study examines the influence of biomass burning on the organic content of urban aerosols in Zagreb, Croatia, by analyzing anhydrosugars, elemental carbon (EC), organic carbon (OC), and water-soluble organic carbon (WSOC) in PM2.5 and PM1 fractions collected during different seasons of 2022. Seasonal trends showed that the highest average concentrations of PM2.5 (27 µg m−3) and PM1 (17 µg m−3) were measured during the winter and decreased in the spring, summer, and autumn, which is in accordance with the specific activities and environmental conditions typical for each season. Different sources of OC and WSOC were noticed across different seasons; levoglucosan (LG) was measured during the winter (1314 ng m−3 in PM2.5 and 931 ng m−3 in PM1), indicating that biomass that was mostly used for residential heating was the main source rather than the agricultural activities that are usually common during warmer seasons. The contribution of LG to PM was 5.3%, while LG contributed to OC by up to 13.4% and LG contributed to WSOC by up to 36.5%. Deviations in typical seasonal variability of LG/WSOC revealed more intense biomass burning episodes during the autumn and several times during the winter season. A back trajectories HYSPLIT model revealed a long-range transport biomass emission source. The levoglucosan-to-mannosan (LG/MNS) ratios indicated the burning of mixed softwood and hardwood during colder seasons and the burning of softwood during warmer seasons. Spearman’s correlation tests and principal component analysis showed a strong and statistically significant (p < 0.05) correlation between LG, PM, OC, EC, and WSOC only during the winter season, demonstrating that they had the same origin in the winter, while their sources in other seasons were diverse.